2016
DOI: 10.1016/j.ijsu.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Total laparoscopic hysterectomy: Analysis of the surgical learning curve in benign conditions

Abstract: A plateau in the learning curve for TLH was reached after the first 75 cases. We can infer that there is a learning curve for TLH as confirmed by the decrease in operating time (accompanied by no change in complications) correlated to gain in experience. On the other hand, one should not disregard the fact that laparoscopy is not a complication-free surgery and achievement of the learning curve does not exclude complications. Gynaecological surgeons can perform TLH securely during the learning curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 24 publications
3
38
0
Order By: Relevance
“…This may result from the patient selection criteria, previous experience of the surgeon in simpler laparoscopic operations and/or difference in surgical technique (We do not routinely perform ureter dissection or perform cystoscopy routinely). However, the uterine weight or the history of pelvic/abdominal surgery, which may create bias, is comparable to the aforementioned studies except for the uterine weight in Terzi et al (10).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…This may result from the patient selection criteria, previous experience of the surgeon in simpler laparoscopic operations and/or difference in surgical technique (We do not routinely perform ureter dissection or perform cystoscopy routinely). However, the uterine weight or the history of pelvic/abdominal surgery, which may create bias, is comparable to the aforementioned studies except for the uterine weight in Terzi et al (10).…”
Section: Discussionmentioning
confidence: 51%
“…However, only a competent surgeon who reached the plateau of the learning curve can serve the virtues of laparoscopy to his/her patients safely. Reaching a plateau in the learning curve and gaining competency in laparoscopic procedures is generally measured by the number of cases operated with a (1) decreased operation time with a (2) acceptable perioperative complication rate, and (3) conversion to laparotomy (8,10,11). Despite the variables such as the difficulty of operations, motivation, and skill of the surgeon, pres-ence of supervision or mentorship, quality and expertise of assisting personnel and equipment quality defining the case number to complete the learning curve is important in the standardization of gynecologists' education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, laparoscopic surgery has a steep and long learning curve. Some studies regarding learning curve of laparoscopic hysterectomy have concluded that 22 to 75 cases were required to reach plateau of learning curve (9)(10)(11). On the other hand, the threshold number has been reported as 20 to 50 cases for RTH (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that gynaecological surgeons can perform LAVH/TLH securely during the learning curve. 13 All the studies on learning curve of laparoscopic hysterectomy were conducted in tertiary care teaching/university hospitals as per literature search. In view of the above, we conducted this retrospective study to analyze the learning curve and clinical efficacy of the art of laparoscopic hysterectomy in a zonal hospital setting (low resource setting) by a single surgeon with basic training in laparoscopy during residency.…”
Section: Introductionmentioning
confidence: 99%